CURRENT CHALLENGES OF THE INTERNATIONAL RELATIONS SYSTEM: IMAGEOLOGICAL AND COMMUNICATION ASPECTS (Coordinates of Public Administration, 2026)
The article provides a thorough analysis of the current challenges of the international relations system in the context of the growing role of image and communication factors. Based on the analysis of Ukrainian and foreign research, it is shown that the formation of the international image of the state increasingly depends on mediatized mechanisms of foreign policy interaction, digital communication tools and global information flows. The transformation of Ukraine's image under the influence of a full-scale war is analyzed, in particular the dynamics of changes in the ratings of «soft power» and national brands, which demonstrate a combination of a sharp increase in international visibility with a subsequent deterioration in complex reputation indicators. The content of the image aspect as a system of knowledge aimed at studying the structure and mechanisms of the reputational capital of the state, and the communication aspect associated with the circulation of political messages, interpretative frameworks and the role of algorithmic platforms in shaping the global agenda are revealed. It is shown that the interaction of these dimensions forms a new analytical matrix within which international relations are considered as a combination of material resources and symbolic-informational mechanisms of influence.Based on empirical data on the Brand Finance ratings, Anholt–Ipsos Nation Brands Index, Global Soft Power Index and research on digital diplomacy, reputational trends characteristic of Ukraine, South Korea and other states are highlighted. The risks of digital mediatization are identified, including information operations, algorithmic polarization and dominance of global platforms. The conclusion is made about the need to transition to long-term state branding strategies focused on stabilizing international trust and information stability.